2018
DOI: 10.1007/s13202-018-0581-x
|View full text |Cite
|
Sign up to set email alerts
|

Mud loss estimation using machine learning approach

Abstract: Lost circulation costs are a significant expense in drilling oil and gas wells. Drilling anywhere in the Rumaila field, one the world's largest oilfields, requires penetrating the Dammam formation, which is notorious for lost circulation issues and thus a great source of information on lost circulation events. This paper presents a new, more precise model to predict lost circulation volumes, equivalent circulation density (ECD), and rate of penetration (ROP) in the Dammam formation. A larger data set, more sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although physics-based models can be used to avoid LCIs, data-driven models offer another layer of information that can be used to estimate or predict unseen events based on historical data from offset drilling operations as well as real-time data collected during drilling operations. In this direction, different machine learning (ML) and deep learning (DL) models have been developed to predict mud loss of circulation from surface parameters [21][22][23][24]. Moazeeni et al [25] reported one of the earliest studies utilizing ML to develop a model capable of predicting LCIs in different areas of a specific oilfield, as well as to estimate the quantity and quality of LCIs.…”
Section: B Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although physics-based models can be used to avoid LCIs, data-driven models offer another layer of information that can be used to estimate or predict unseen events based on historical data from offset drilling operations as well as real-time data collected during drilling operations. In this direction, different machine learning (ML) and deep learning (DL) models have been developed to predict mud loss of circulation from surface parameters [21][22][23][24]. Moazeeni et al [25] reported one of the earliest studies utilizing ML to develop a model capable of predicting LCIs in different areas of a specific oilfield, as well as to estimate the quantity and quality of LCIs.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…We applied MAF twice for each feature with ∈ [24,48] records, which correspond to [2,4] minutes, respectively, in the most common data frequency of 0.2 Hz. This allows for two levels of macroscopic trends and also two denoising stages, which the ML/DL model can learn from during training.…”
Section: ) Feature Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Drilling fluid is very important in the drilling operation. If the drilling fluid was not designed properly, many unwanted consequences can happen such as lost circulation and stuck pipe issues (Alkinani et al 2019;Al-Hameedi et al 2018). To obtain the desired properties, chemical and non-biodegradable materials have been the traditional additives that are used in drilling fluids.…”
Section: Introductionmentioning
confidence: 99%